Molecular monitoring of Escherichia coli O157: H7 sterilization rate using qPCR and propidium monoazide treatment. (25th February 2013) - Xing‐long, X.; Cong‐cong, L.; Yang, Q.; Yi‐gang, Y.; Hui, W.
Abstract Propidium monoazide is a DNA‐intercalating dye. PMA‐qPCR has been reported as a novel method to detect live bacteria in complex samples. In this study, this method was used to monitor the sterilization effects of UHP, ultrasound and high PEF on Escherichia coli O157:H7. Our results showed that all three sterilization techniques are successful to kill viable E. coli O157:H7 cells under their appropriate conditions. PMA‐qPCR can effectively monitor the amount of DNA released from viable E. coli O157:H7 cells, and the results from PMA‐qPCR were highly consistent with those from plate counting after treatment with UHP, ultrasound and high PEF. The maximal ΔCt between PMA‐qPCR and qPCR obtained in this study was 10·39 for UHP, 5·76 for ultrasound and 2·30 for high PEF. The maximal sterilization rates monitored by PMA‐qPCR were 99·92% for UHP, 99·99% for ultrasound and 100% for high PEF. Thus, PMA‐qPCR can be used to detect the sterilization effect on food and water supplies after treatment with UHP, ultrasound and high PEF.